Probationary Period Provisions in the Saudi Labor System (International Journal of Financial, Administrative and Economic Sciences, 2024)
The labor system and its rules governing employment relations constitute a branch of law widely applicable in practical settings. This has led to the emergence of the probationary period clause, meeting the needs of parties in certain employment contracts. The study highlights the practical significance of the probationary period clause in employment contracts, particularly its impact on terminating employment without just cause. Therefore, the study emphasizes the importance of examining the probationary period clause and delineating the parties' rights within the employment contract. The main issue addressed in the study pertains to the provisions of the probationary period clause, notably concerning the omission in the law regarding the employee's entitlement to annual leave pay and the employer's right to terminate a female employee during maternity leave. The study employs an analytical approach by reviewing the provisions of Saudi labor law regulating probationary period clauses. It concludes that during the probationary period, termination results only in the loss of compensation and end-of-service benefits, but it does not explicitly forfeit the right to annual leave pay. Additionally, the law does not clearly grant the employer the right to terminate a female employee during maternity leave, despite explicitly prohibiting absolute termination during this period. The study recommends clarifying whether the probationary period counts towards the accrued period for annual leave pay calculation and suggests attaching conditions to the termination of employment during probation, ensuring the employee's right not to be dismissed while on maternity leave.
Keywords: Work System; Labor Relations; Probation Period